Economic Theory and Socialist Economy - Lerner, A. P. (Review of Economic Studies, 1934)
Journal Article Economic Theory and Socialist Economy Get access A. P. Lerner A. P. Lerner London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 1, October 1934, Pages 51–61, https://doi.org/10.2307/2967550 Published: 01 October 1934